ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG PADA PT NIAGA RAYA SAMARINDA - Camelia Verahasuti3, Nurhayati1 Mulyadi2 (EKONOMIA, 2021)
ABSTRACTInventory of merchandise is a very important component in the operational activities of companies engaged in trade. Internal control system of inventory must be carried out in order to avoid any errors that occur due to human error (Human Error) in the case of wrong receipt, storage,expenditure, inventory calculation, it is necessary to have a physical check (stock taking) periodically, arranging inventory according to its type, and the division of functions and tasks for each section. The purpose of this thesis research is to get a clear picture of the internal control system of merchandise inventory implemented by the company. The author analyzes the internal control system of merchandise inventory at PT. Niaga Raya Samarinda with the Comparative Method (comparison), which compares the internal control system established by the company with the internal control system according to the literature and uses a flow chart. The interview process is also attached in the form of a questioner which means that according to the data using question and answer or interview with the relevant parts, namely the receipt and release of goods (1 person) and the warehouse (4 people).The results of the analysis mentioned the inventory accounting systems and procedures at PT. Niaga Raya Samarinda is good enough to meet good internal control supported by the results of the questioner of 37 question items with an answer score of 57.279% yes this means PT. Niaga Raya Samarinda is sufficient to meet the elements of a good internal control system. However, there are some things that need to be considered, namely physical inspection (stock taking) on a regular basis, the preparation of inventory according to its type, as well as the division of functions and tasks for each section. Based on the above it can be seen that the hypothesis proposed by the author is rejected, because the internal inventory control system implemented by the company has been implemented quite well.